Web2forDev: Sharing information [web 2.0] - Ballantyne, Peter G. (Technical Centre for Agricultural and Rural Cooperation, 2007)
A growing range of web 2.0 applications is revolutionizing how information can be accessed and shared. The experience of Euforic shows how these tools can be applied to increase content on a website while still keeping costs low.